Rearing of Green Catfish Larvae (Hemibagrus nemurus) With Different Protein Source of Paste Feed - Imam Muliana Rusin; Hamdan Alawi; Nuraini ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research on rearing of green catfish larvae (Hemibagrus nemurus) with different protein source of paste feed was carried out for 40 days in the Laboratory of Fish Hatchery and Breeding Faculty of Fisheries and Marine Sciences University of Riau. The aim of this study was to evaluate the substitution of tubifex worm with different protein sources of paste feed. Protein sources used were squid meal, fish meal, cockle meal and mysid meal. The effect on growth and survival was determined.Result showed that tubifex worm cauld not be substituted by the paste feed in rearing green catfish larvae for 40 days rearing period. Among the paste feed, the squid meal protein source paste feed was the best and more efficient in term of highest survival rate and the lowest cost per fish.Keywords: paste feed, growth, survival Hemibagrus nemurus larva